The Effectiveness of Market Management In Increasing Customer Satisfaction at Pondok Labu Market In Pondok Labu Kelahan Cilandak Sub-District Jakarta Selatan - Nurdiyanti Nurdiyanti; Deti Mulyati; Marja Sinurat (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
The writing of this thesis aims to find out how the actual process and conditions of market structuring activities at PD Pasar Jaya Pasar Pondok Labu, where Pondok Labu market conditions are less conducive and irregular with less organized conditions in the Pondok Labu market area which causes Pondok Labu Market conditions disturbed. With the rearrangement based on the lack of previous implementation, it can reduce and even eliminate the negative impacts that arise due to unfavorable and irregular market conditions, as well as re-functioning of the facilities and infrastructure around the Pondok Labu Market so that it can be used and functioned as it should. Research method used is descriptive method using a qualitative analysis approach, and this research was carried out on the implementation of market structuring in this case Cilandak Sub-district. Pondok Labu Market management research uses the concept of goal approach, systems perspective and individual behavior in the organization. Based on the results of the study, the market arrangement in Pondok Labu Market, Pondok Labu Sub-District, Cilandak Sub-District runs smoothly and effectively where the arrangement follows the objectives and objectives of the arrangement, although there are some obstacles and constraints. This obstacle can be overcome by the coordination of various related agencies in the Pondok Labu market structuring activities so that the infrastructure in the Pondok Labu market area can function properly he Government in this case Cilandak Subdistrict accelerates the provision of places / locations and revitalizes adequate locations for street vendors so that they do not return to facilities and infrastructures and provide socialization and appeals to the new traders who occupy the infrastructure that has been trimmed so as not to occur violation.